N-Acylethanolamine acid amidase (NAAA) inhibitor F215 as a novel therapeutic agent for osteoarthritis. (July 2019) - Zhou, Pan; Xiang, Lei; Yang, Yulong; Wu, Yuezhou; Hu, Ting; Liu, Xiaolong; Lin, Feitai; Xiu, Yanghui; Wu, Kangni; Lu, Canzhong; Ren, Jie; Qiu, Yan; et al.
Graphical abstract: Abstract: Osteoarthritis (OA), characterized by cartilage damage, synovitis inflammation and chronic pain, is a common degenerative joint disease that may lead to physical disability. In the present study, we first explored the association between N-Acylethanolamine acid amidase (NAAA) and OA progression, and then examined the capability of the NAAA inhibitor F215 to attenuate osteoarthritis. Increased NAAA expressions and decreased PEA levels in synovial membrane and lumbar spinal cord were observed in MIA induced osteoarthritic rats. F215 ( i.a., and i.p. ) significantly protected against cartilage damage and synovial inflammation by directly increasing PEA levels in joints, or normalization of PEA levels and resolution of inflammation in spinal cord. Moreover, F215 also markedly alleviated osteoarthritic pain in rats, and the therapeutic effects of F215 were blocked by the PPAR-α antagonist MK886. The results revealed that NAAA may has been implicated in OA progression, and treatment with NAAA inhibitor F215 alleviated OA development by preventing cartilage damage, reducing inflammation, and alleviating pain. Our study suggested that NAAA inhibitor might be a novel therapeutic agent for OA treatment.